2016
DOI: 10.1016/j.eurpsy.2016.01.1334
|View full text |Cite
|
Sign up to set email alerts
|

The association between childhood trauma and facial emotion recognition in patients with stable schizophrenia

Abstract: IntroductionThe impairment of facial emotion recognition (FER) among patients with schizophrenia (SCZ) is a significant feature of the illness. Childhood trauma (CT) is reported with a high prevalence in SCZ and is considered one of its risk factors.ObjectivesTo investigate the relationship between FER and CT in SCZ.MethodsFifty-eight outpatients with stable SCZ completed the Childhood Trauma Questionnaire retrospectively assessing five types of childhood trauma (emotional, physical and sexual abuse, and emoti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Furthermore, the authors suggested that the type of abuse could be associated with specific emotion recognition deficits. In particular, in this study, sexual abuse was associated with poor recognition of anger and disgust, and emotional abuse and physical neglect were associated with poor recognition of happy and sad faces (169).…”
Section: The Impact Of Comorbid Ace and Primary Psychosis On Facial Ementioning
confidence: 48%
See 2 more Smart Citations
“…Furthermore, the authors suggested that the type of abuse could be associated with specific emotion recognition deficits. In particular, in this study, sexual abuse was associated with poor recognition of anger and disgust, and emotional abuse and physical neglect were associated with poor recognition of happy and sad faces (169).…”
Section: The Impact Of Comorbid Ace and Primary Psychosis On Facial Ementioning
confidence: 48%
“…On the one hand, an enhanced neural processing of negative stimuli [i.e., increased brain activity; (170)] has been reported, but this does not seem to translate in improved behavioral processing. Indeed, behaviorally, individuals with primary psychosis, and a history of ACE perform significantly worse on emotion recognition tasks than adults with primary psychosis without ACE exposure (169). This pattern may suggest that ACE may further boost the general aberrant salience in primary psychosis, thereby causing overarousal and impeding a differentiated behavioral facial expression processing performance.…”
Section: Need For Integrative Studies Across Multiple Clinical Conditmentioning
confidence: 99%
See 1 more Smart Citation